2021
DOI: 10.3390/nu13072162
|View full text |Cite
|
Sign up to set email alerts
|

Role of Herbal Teas in Regulating Cellular Homeostasis and Autophagy and Their Implications in Regulating Overall Health

Abstract: Tea is one of the most popular and widely consumed beverages worldwide, and possesses numerous potential health benefits. Herbal teas are well-known to contain an abundance of polyphenol antioxidants and other ingredients, thereby implicating protection and treatment against various ailments, and maintaining overall health in humans, although their mechanisms of action have not yet been fully identified. Autophagy is a conserved mechanism present in organisms that maintains basal cellular homeostasis and is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 280 publications
(315 reference statements)
0
9
0
Order By: Relevance
“…The main advantage of functional products is a mild correction of a lack of vitamins, minerals, antioxidants, and other nutraceuticals without fear of excessive consumption [ 4 , 5 , 6 ]. Widely used functional products are functional beverages, namely herbal teas, which have pleasant organoleptic properties and a positive biological effect [ 7 ]. The application of fermentation to create plant-based beverages is the most commonly used process.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of functional products is a mild correction of a lack of vitamins, minerals, antioxidants, and other nutraceuticals without fear of excessive consumption [ 4 , 5 , 6 ]. Widely used functional products are functional beverages, namely herbal teas, which have pleasant organoleptic properties and a positive biological effect [ 7 ]. The application of fermentation to create plant-based beverages is the most commonly used process.…”
Section: Introductionmentioning
confidence: 99%
“…The polyphenols contain multiple functional components, such as (-)-epigallocatechin gallate (EGCG) and theaflavin (TF) (25,26), which were reported to have anti-inflammatory and antioxidant effects, and other biological properties (5,27). Also, multiple in vitro and in vivo studies have indicated that several oolong tea polyphenol extracts could induce apoptosis or proliferation of cancer cells, including oral cancer cells, leading to tumor growth inhibition (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin gallate (EGCG) is the most abundant green tea polyphenol with numerous health benefits [ 79 , 80 , 81 , 82 ]. In colorectal carcinoma cells (HT-29), EGCG induced autophagy to inhibit the proliferation of cells through the regulation of the glycerophospholipid metabolic pathway [ 83 ].…”
Section: Roles Of Polyphenols In Autophagic Adaptation For Healthy Agingmentioning
confidence: 99%